PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN MELAKUKAN SHOLAT SISWA SEKOLAH DASAR - Fauzi Ahmad Syawaluddin; Jailani Syahputra Siregar; Betti Megawati; Samsir Samsir (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2021)
The research aims to see how the influence of developing interactive multimedia-based learning media is to improve the ability to pray. The focus of research for fourth-grade students at SD Negeri 115525 Sigambal. The material to be packaged is the primary material and the core of learning to pray. The packaged components are sound audio, visualization of images, videos, animations, and sentences or text. The teaching media section consists of introductions, media information assistance, teaching materials, assignments, and exam questions. The media is equipped with a button that makes the media move between the sheets of teaching media. Research methods R&D or Research and Development. Field test with the Guttman Scale for smooth scoring. The Guttman scale will generate action with a definite value, divided into two choices, yes or no. The effect of developing interactive multimedia-based learning media can improve the ability to pray for fourth-grade students at SD Negeri 115525 Sigambal has been recognized as eligible to be a teaching medium for grade four elementary school students at SD Negeri 115525 Sigambal